Aspiring to be : the tribal, indigenous condition - Roy Burman, B. K.; Verghese, B. G.; Commonwealth Human Rights Initiative; Minority Rights Group; Workshop on the Rights of Tribal and Indigenous Peoples (1996 : New Delhi, India) (Delhi : Konark Publishers, 1998)
Papers presented at a Workshop on the Rights of Tribal and Indigenous Peoples held in New Delhi, February 23 to 25, 1996.
"Under the auspices of Commonwealth Human Rights Initiative, New Delhi and Minority Rights Groups, London."
Includes bibliographical references and index.
Keywords: India -- Scheduled tribes -- Social conditions; India -- Scheduled tribes -- Economic conditions